The Warren Buffett way - Hagstrom, Robert G. 1956- (Wiley, 2014)
"The bestselling book on Warren Buffett returns, with new insights on his continued successOften described as the greatest investor of all time, Warren Buffett grew a $100 investment in the late 1950s into an investment empire. In the process, he has become one of the wealthiest individuals in the world, and the foremost authority on investing of our generation.With over one million copies sold, The Warren Buffett Way is the definitive book on "The Oracle of Omaha's" investment methods. Completely revised and updated, the Third Edition of The Warren Buffett Way focuses on the timeless principles and strategies behind Buffett's extraordinary investment success. This edition contains new chapters on the important distinctions between investing and trading, as well as an examination of the most successful disciples of Warren Buffett. Throughout the book, fresh examples and case studies are used and Buffett's successful formula is distilled in a way that will provide value to readers for decades to come. This edition represents the totality of Buffett's investment career and focuses on his timeless investing principles Companion website contains "Buffett Investment Calculators," which you can use to calculate the value and investment potential of companies Written by foremost Buffett expert Robert Hagstrom Engaging and informative, the Third Edition of The Warren Buffett Way is a must read--not just for avid Buffett fans, but for anyone who wants to know what it takes to make the best investment decisions possible"--
Includes index
Description based on print version record
Keywords: Buffett, Warren; Buffett, Warren -- 1930-; Capitalists and financiers -- United States -- Biography; Investments -- United States; Strategie; Aktienanlage; USA; Biografie